Influence of Fuel to Oxidizer Ratio on Microwave-Assisted Combustion Preparation of Nanostructured KOH/Ca12Al14O33 Catalyst Used in Efficient Biodiesel Production - Nayebzadeh, Hamed; Haghighi, Mohammad; Saghatoleslami, Naser; Tabasizadeh, Mohammad (Frontiers in Energy Research, 2020)
In this study, the microwave-assisted solution combustion method was utilized for the fabrication of Ca12Al14O33 as support and the amount of urea was assessed as an important parameter during synthesis of the sample. Synthesized Ca12Al14O33 with different fuel amounts was impregnated by KOH and used in the biodiesel production process with canola oil under microwave irradiation. The results presented that the crystallinity, crystalline size, specific surface area, and elemental composition of the final nanocatalysts are affected by the fuel amount. Moreover, during impregnation of potassium components, the structure of support was interestingly transformed from CaAl2O4 to Ca12Al14O33 structure due to the incorporation of potassium in an alumina lattice and more diffusion of calcium cations into a support lattice. On the other hand, when the amount of fuel passed the optimum amount (2 times the stoichiometric amount), the crystallinity was reduced due to the formation of high amounts of smoke during combustion and prevention of the entry of air (oxygen) into the system. The results of the microwave-enhanced transesterification reaction confirmed the results of the analyses that the conversion of 94.5% was obtained using an optimum sample at 450 W, 12 molar ratios of methanol/oil, 4 wt.% catalyst, and 60 min reaction time. According to the stability of the optimum sample [at least three times (>75%)], along with its unique mesoporous structure, uniform dispersion of potassium components, and high basicity sites, it can be considered as a comparable solid base nanocatalyst for biodiesel production.